The Effect of Readability of Annual Reports and Value Relevance of Financial Information on Agency Costs with Analyst Coverage as Moderating Variable - Stefan Soesanto; Hendra Wijaya (Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of readability based on the length of the annual report and the value relevance of the financial information on agency costs. The sample used in this study were 263 firm-year from Kompas100 index. Data were analyzed using multiple linear regression method. The result of this study indicate that the higher the number of pages, words and characters, which reflects the poor readability of the annual report, has a negative effect on the asset turnover ratio, which is an inverse proxy for agency costs. Furthermore, the presence of the analyst coverage variable is able to moderate the positive effect between the number of pages, words and characters in the annual report on the asset turnover ratio. However, no significant effect was found during both test between value relevance to asset turnover ratio and that are moderated by analyst coverage.